2014
DOI: 10.1155/2014/615895
|View full text |Cite
|
Sign up to set email alerts
|

Renal Medullary Carcinoma: Case Report of an Aggressive Malignancy with Near-Complete Response to Dose-Dense Methotrexate, Vinblastine, Doxorubicin, and Cisplatin Chemotherapy

Abstract: Renal medullary carcinoma (RMC) is a rare but aggressive malignancy affecting young individuals with sickle cell trait. Renal medullary carcinoma commonly presents with advanced or metastatic disease and is associated with a rapidly progressive clinical course and an extremely short overall survival measured in weeks to few months. Due to the rarity of RMC, there is no proven effective therapy and patients are often treated with platinum-based chemotherapy. We report near-complete radiological and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Recently, Amjad et al [21] reported a case where a 23-year-old African American patient with sickle cell anemia had a near complete clinical and pathological response to ddMVAC. This particular patient had six cycles of neoadjuvant ddMVAC with great tolerance and no need of hospitalization, and then proceeded with a total nephrectomy with retroperitoneal lymphadenectomy, showing a near complete pathological response, developing recurrence only 16 months later [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Amjad et al [21] reported a case where a 23-year-old African American patient with sickle cell anemia had a near complete clinical and pathological response to ddMVAC. This particular patient had six cycles of neoadjuvant ddMVAC with great tolerance and no need of hospitalization, and then proceeded with a total nephrectomy with retroperitoneal lymphadenectomy, showing a near complete pathological response, developing recurrence only 16 months later [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Amjad et al [21] reported a case where a 23-year-old African American patient with sickle cell anemia had a near complete clinical and pathological response to ddMVAC. This particular patient had six cycles of neoadjuvant ddMVAC with great tolerance and no need of hospitalization, and then proceeded with a total nephrectomy with retroperitoneal lymphadenectomy, showing a near complete pathological response, developing recurrence only 16 months later [21]. Another case report from Alabama University described an 11-year-old African American patient who was submitted to three cycles of neoadjuvant carboplatin, gemcitabine and paclitaxel, followed by a right nephrectomy with an aortocaval lymphadenectomy and multiple nodule resections of the lungs, with no evidence of diseases on the surgical specimens of the lymph nodes and pulmonary nodules.…”
Section: Discussionmentioning
confidence: 99%
“…34 RMC was first identified by the Genitourinary Pathology Department, Armed Forces Institute of Pathology, Washington, DC, USA in 1995, where it was recognized as "the seventh sickle cell nephropathy", adding to a list that includes gross hematuria, papillary necrosis, nephrotic syndrome, renal infarction, the inability to concentrate urine, and pyelonephritis. 35 The original study reported a mean patient age of 22 years, with a male predominance of 2:1.…”
Section: Renal Medullary Carcinoma Backgroundmentioning
confidence: 99%
“…Its codes for protein INI1 (hSNF5/SMARCB1/BAF47) which is present in all normal tissues from yeasts to humans. It is involved in transcriptional activation and repression by chromatin remodeling and also interacts with other cancer associated pathways like WNT signaling pathway and hedgehog signaling pathway [11,12,13]. Mutation of this gene resulting in loss of expression is seen in RMC which is hence also called SMARCB 1 deficient renal medullary carcinoma.…”
mentioning
confidence: 99%